Pendidikan Islam Transdisipliner dan Sumber Daya Manusia di Madrasah Tsanawiyah Negeri Kota Depok - Dwi Kartika Susanti; Adi Fachrudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This description may lead to educational opportunities. Islam was conducted in an open and transdisciplinary fashion, which means it disregards the distinction between general knowledge and the science of religion and recognizes the interconnectedness of all developed sciences. The employed methodology is the discourse and content analysis technique. The manner in which a variety of literature is thoroughly investigated and analyzed in accordance with the intent and direction of the transdisciplinary concept. Evidently, with regard to the field of education The Islamic transdisciplinary curriculum that ought to be formulated should possess a holistic approach, encompassing a wide range of issues that are inherent to humanity and its development, including self-improvement and human resource management. Understanding man as a mysterious organism requires interdisciplinary scientific inquiry; it cannot be comprehended through the lens of a single scientific discipline alone. The anticipated outcome of a transdisciplinary Islamic education is the development of the capacity to perceive the world as a system of values, each of which possesses distinct responsibilities and functions that are inextricably intertwined. This is connected to the system. Frame it in the splendor of faith and principles.